THE STUDENT-CENTERED LEARNING APPROACH AND THE DEVELOPMENT OF 21ST-CENTURY SKILLS - Yelna Septiana; Hafizh Maulana Nugraha; Muhammad Sirozi (LP2M IAI Al-Khairat Pamekasan, 2026)
This study aims to analyze the urgency of appropriate learning approaches, the relevance of the Student-Centered Learning (SCL) approach, and its advantages in developing 21st-century skills. The transformation of 21st-century education requires a shift from teacher-centered learning to student-centered learning, emphasizing the 4C skills (critical thinking, creativity, collaboration, and communication). This research employs a qualitative approach using a literature review method by examining 23 relevant scientific sources, including national journals, books, and proceedings. Data analysis was conducted through content analysis involving data reduction, categorization, synthesis, and conclusion drawing. The findings indicate that appropriate learning approaches play a fundamental role in improving the quality of learning processes and outcomes. The SCL approach demonstrates strong theoretical and practical alignment with the 21st-century skills framework by promoting active engagement, independence, and critical and collaborative thinking. Furthermore, SCL offers advantages in creating meaningful, contextual, and flexible learning while supporting authentic assessment practices. Therefore, SCL is an effective approach for developing adaptive competencies aligned with global demands.